Efektivitas Konseling Kelompok Berbasis Cognitive Restructuring dalam Menurunkan Quarter-Life Crisis Siswa SMK NU Kedungtuban - Putri Safitya; Ah. Fahri Munir; Moh. Yusuf Efendi (Indonesian Journal of Educational Counseling, 2026)
Quarter-life crisis is a psychological condition characterized by anxiety, self-doubt, confusion, feelings of being trapped, and uncertainty in making decisions about the future. This condition may occur among vocational high school students who are in the transition period from school to employment or higher education. This study aimed to examine the effectiveness of group counseling using cognitive restructuring techniques in reducing quarter-life crisis among students of SMK NU Kedungtuban. This research employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The population consisted of 110 twelfth-grade students, while the initial screening involved 84 students. Based on the screening results, 10 students with high levels of quarter-life crisis were selected as treatment subjects through purposive sampling. Data were collected using a quarter-life crisis psychological scale and analyzed using a paired sample t-test. The results showed a decrease in the mean score from 149.40 in the pretest to 132.80 in the posttest, with a mean reduction of 16.60 points. The paired sample t-test produced a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. These findings suggest that group counseling using cognitive restructuring techniques is effective in reducing quarter-life crisis among vocational high school students.